Pengaruh Insektisida Diazinon 600 EC Terhadap Fekunditas dan Viabilitas Kokon Cacing Tanah Pontoscolex corethrurus Fr. Mull - Putri, Dewinda Yanua; Sumarmin, Ramadhan; Nursyahra, Nursyahra (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ The use of insecticide often exceed the dose should be in addition to harmful to health, the environment and also have an impact on-non target animal, one of them earthworm. This study on the effect of the insecticide Diazinon 600 EC to fecundity and viability of earthworm cocoons Pontoscolex corethrurus Fr. Mull. It has been conducted in-July â Augustus 2013, housed in the zoology laboratory biology, Padang State University.This research Â is an experiment using the Completely Randomized Design (CRD) with 4 treatments 6 replications. The treatmens were Diazinon 600 EC with 0 g/l (A), 0,002 g/l (B), 0,004 g/l (C), and 0,006 g/l (D) mixed with media. Parameters in this study were the fecundity and viability of earthworm cocoons Pontoscolex corethrurus Fr. Mull.The average number of cocoons fecundity and viability of earthworm cocoons Pontoscolex corethrurus Fr. Mull found highest in treatment A (40) and the lowest cocoons treatment D (0). While the average percentage hatchability Pontoscolex corethrurus earhworm cocoons were highest inÂ A, B, and C were 100% and the lowest concentration of D(0 %). It can coucluded that the insecticide Diazinon 600 EC can reduce fecundity cocoon, but had no effect on the viability of earthworm cocoons Pontoscolex corethrurus Fr. Mull.Â Â